Concevoir des objets techniques pour une population normale, c’est-à-dire comprenant aussi des personnes handicapées ou très âgées - Jean-Claude Sperandio (Perspectives Interdisciplinaires sur le Travail et la Santé)
Technologies can be formidable obstacles for disabled people or the elderly, or inversely, can also provide effective solutions to the problems that these people encounter. This involves all the usual objects of daily life, but also assistive devices, lodging, public transportation, workstations, etc.Many special redesigns or particular assistive devices would be unnecessary if the initial design of objects or services intended for the general public had taken into account disabled people or the elderly in the general population. Ergonomics can contribute to the design of assistive devices and services more easily usable by handicapped people